Galanin receptor 2 modifies neuropeptide Y Y1 receptor internalization and β-Arrestin recruitment - Narváez-Peláez, Manuel; Borroto Escuela, Dasiel Óscar; Millón-Peñuela, Carmelo; Flores-Burgess, Antonio; Gago-Calderón, Belén; Santín-Núñez, Luis Javier; Fuxe, Kjell; Narváez-Bueno, José Ángel; Díaz-Cabiale, Zaida (My University, 2015)
We have recently described a Galanin receptor 2(GALR2) and Neuropeptide Y Y1 receptor(NPYY1R) interaction at behavioural, cellular and receptor levels through GALR2/NPYY1R heterodimers. The aim of this work was to study if GALR2 and NPYY1R costimulation modified NPYY1R internalization and β-Arrestin recruitment after in HEK293T cells. HEK293T cells were transfected with NPYY1REGFPor β-Arrestin2GFP2 cloned with standard molecular biology techniques employing PCR and fragment replacement strategies. NPYY1REGFP/GALR2 and NPYY1R/GALR2 with β- Arrestin2GFP2 HEK293T coexpressing cells were incubated with NPY 1μM and/or GAL1μM, at different times. Antagonist studies were performed 15 min prior to the addition of agonist with NPYY1R antagonist BIBP3226 10μM or GALR2 antagonist M871 10 μM. Timed-interval images of NPYY1REGFP or β-Arrestin2GFP2 endosomes in different cell groups were acquired using a confocal microscope following agonist addition. Percentage of internalization was determined by Leica software analysis of total membrane fluorescence compared to total internal compartment fluorescence at the various time points. We observed that addition of NPY induced a rapid decrease in the cell surface expression of NPYY1REGFP and a redistribution of β-Arrestin2GFP2. In fact, we observed a maximum of internalization of 80% three minutes after the NPY stimulation. However, combined treatment with GAL and NPY induced a delay in the internalization of NPYY1REGFP, with a maximum of internalization thirty minutes after the co-stimulation. Moreover, a delay in the β-Arrestin2GFP2 redistribution was observed. The specific GALR2 antagonist M871 abolished these delays in internalization of NPYY1REGFP and β-Arrestin2GFP2 redistribution, suggesting that this effect was mediated through the coactivation of GALR2 and NPYY1R. These results demonstrate that costimulation with GAL and NPY delays the internalization of ￼ NPYY1REGFP by decreasing recruitment of β-Arrestin2GFP2 and probably could change intracellular signaling. This study was supported by Junta de Andalucia CVI6476.
Keywords: Neuropéptidos; Ansiedad; Neuropéptido; Interacción receptores; Galanina